CytoSorb® therapy: a new approach to treat critically ill patients with COVID-19 – a retrospective study - K. Patil; M. Priyadarsini (International Journal of Medical Device and Adjuvant Treatments, 2023)
Objective: The Coronavirus 2019 (COVID-19) pandemic has resulted in significant mortality and morbidity. Patients with severe COVID-19 infection experience cytokine storm that makes the treatment approach more challenging. The aim of the present study was to evaluate the effects of CytoSorb® therapy in COVID-19 patients admitted in ICU.